(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Rapid urbanization has intensified the need for innovative approaches to address environmental, social, and infrastructural challenges in cities. Smart city initiatives, drive n by advanced technologies and data informed governance, offer pathways toward sustainable urban development. This study examines the pivotal role of local governments in conceptualizing, implementing, and sustaining such initiatives. Using a mixed methods approach, three representative cities were analyzed through policy review, stakeholder interviews, and citizen surveys. Findings reveal that cities with integrated sustainability frameworks, active stakeholder engagement, and adaptive policy mechanisms ac hieve higher performance in energy efficiency, waste reduction, and citizen satisfaction. Conversely, initiatives focusing predominantly on technological deployment without inclusive governance show limited societal benefits. The study underscores the impo rtance of aligning technology adoption with environmental stewardship, social equity, and economic growth to maximize the transformative potential of smart cities.